Local Wisdom Values in Turun karai Tradition in Sibuluan Nalambok Village, Central Tapanuli Regency, North Sumatra Province - Wahyu Novita Panggabean; Endrizal; Emzia Fajri (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The research entitled "Local Wisdom Values in the Turun Karai Tradition in Sibuluan Nalambok Village, Central Tapanuli Regency, North Sumatra Province". The background of the Turun Karai tradition is to honor the birth of the Prophet Muhummad SAW. The purpose of this study is to find out how the implementation of the Turun Karai tradition and what local wisdom values are in this Turun Karai. The theory used in this research is the theory of tradition in Soebadio's thinking and the theory of local wisdom according to Widieharto, Prasetyo and Kumalasari's understanding where this theory is used to understand local wisdom and local wisdom values contained in the Turun Karai tradition. This research uses a qualitative method. The results of this study explain the procession of implementing the Turun Karai tradition and the local wisdom values that exist in the Turun Karai tradition. The procession is carried out when the baby is one month old and has several stages, namely the first stage of preparation, such as decorating the house, cooking food and filling dulang. The second stage is the implementation of turun karai, bringing the child to the mosque then lowering the child's feet for the first time, conducting a procession of bargaining flour, distributing itak-itak, naming the child, mambuekan the child, cutting the hair, and mangupa-upa. The last stage is distributing singgang ayam to all members of the recitation and the invited guests eat the food that has been served. Furthermore, there are local wisdom values in the Turun Karai tradition, namely religious values, gotong royong values, aesthetic values, moral values and tolerance values.